The Social Construction Behind the Merah Putih Village Cooperative - Fauzi Fauzi; Mursyidin Mursyidin; Nur Hafni; Riza Hasan; Iskandar Zulkarnaen (El-Usrah: Jurnal Hukum Keluarga, 2026)
The purpose of this study is to analyze the social construction and community perceptions of the Red and White Village Cooperative (KDMP) program, specifically in Bener Meriah Regency, Aceh. The study employed a mixed methods approach. Qualitative data collection involved interviews and focus group discussions with 35 key informants. Quantitative data collection involved distributing questionnaires to 200 respondents. Data were analyzed using descriptive and inferential methods to evaluate the potential and challenges of the KDMP program. The study found that the KDMP emerged as a manifestation of the collective desire to build economic independence, strengthen local identities based on agriculture, such as Gayo coffee, and create a space for togetherness based on solidarity. Based on the social construction analysis, this study concludes that Bener Meriah residents' perceptions of the establishment of the KDMP show a significant difference, namely between hopes for it as a vehicle for strengthening the village economy and skepticism. These perceptions are then formed through a process of externalization, institutional objectification, and internalization of experience. The majority of respondents expressed positive support for the KDMP. However, negative comments cannot be ignored. Negative perceptions of the KDMP usually contain criticism, doubt, and concerns about the consequences of suboptimal cooperative management, especially regarding small businesses and the local economy.